Survey Results Durability labelling - Moreno Beguerisse, Mariale (Cranfield University, 2017)
Results of a survey that look into attitudes and behaviours of people towards purchasing, use and dispose of workhorse products to design a durability label
Keywords: durability labelling'; 'workhorse products'; 'appliances'; 'product lifespan'; 'electric and electrical appliances'; 'Environment Policy'; 'Family and Household Studies'